Comparing marine primary production estimates through different methods and development of conversion equations - Regaudie-de-Gioux, Aurore; Lasternas, Sébastien; Agustí, Susana; Duarte, Carlos M. (Frontiers in Marine Science, 2014)
Numerous studies have compared the rates of primary production using various techniques at specific locations and times. However, these comparisons are local and cannot be used to compare or scale rates of primary production using different methods across ocean basins or seasonal time scales. Here, we quantify the range in rates of primary production derived using different techniques and provide equations that allow conversions of estimates between different methods. We do so on the basis of a compilation of data on volumetric estimates of primary production rates concurrently estimated with at least two different methods. We observed that the comparison of estimates of marine phytoplankton primary production derived from different methods reveals very large variations between methods. The highest primary production estimates are derived using the 18O method, which may provide the best and more generally applicable estimate of gross primary production. The regression equations presented in this work provide the best available approach to convert data across methods and therefore integrate and synthesize available and future data derived using different methods.